Analisis Kinerja Program Studi Manajemen Terhadap Kompetensi lulusan Universitas Terbuka - Febrisi Dwita; Deni Surapto; Irmawati Irmawati; Leony Agustine (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2022)
Abstract: The success of the Study Program is judged by the academic quality offered by the programs so that it can produce graduates who have competencies according to the field of science being studied and are able to compete in the workforce and can play a role in the community. To be able to carry out learning activities properly, the factors that must be considered include: student characteristics, courses, program objectives, geography, technology, scale, and management system. From the aspect of performance quality, UT graduates are expected to improve their self-development skills (advanced studies), leadership skills and teaching skills which in the end the performance of UT graduates has innovative behavior, responsibility, and achievement in work. Respondents consist of graduates and superiors. Quantitative descriptive analysis method was used to describe the results obtained from distributing questionnaires both online and offline. The data obtained will be presented through tables or charts that can explain the attitudes and behavior of graduates and graduate superiors. The results of the study show that the contribution of universities to competence after graduation is 19.5%, especially prioritizing the ability in the field of knowledge that has been provided during this study period as a provision in competition in the world of work and business, followed by learning abilities and research abilities and critical thinking. The next competencies are in terms of increasing the ability to speak English by 9%, the internet, the ability to operate computers and leadership. And the last is competence outside the field of science of 0.81. Keywords: Performance, Study Program, Competence.